2011
DOI: 10.1007/s11258-011-9926-y
|View full text |Cite
|
Sign up to set email alerts
|

Understory response to varying fire frequencies after 20 years of prescribed burning in an upland oak forest

Abstract: Ecosystems in the eastern United States that were shaped by fire over thousands of years of anthropogenic burning recently have been subjected to fire suppression resulting in significant changes in vegetation composition and structure and encroachment by invasive species. Renewed interest in use of fire to manage such ecosystems will require knowledge of effects of fire regime on vegetation. We studied the effects of one aspect of the fire regime, fire frequency, on biomass, cover and diversity of understory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…It has been suggested that fire only causes short term changes in soil microbial communities while larger changes may be driven by vegetation dynamics (Hart et al, 2005). Therefore, differences in soil microbial communities were presumably indirectly related to burning through changes to nutrient and substrate availability via changes in aboveground vegetation observed at the same site (Burton et al, 2010(Burton et al, , 2011. There were no correlations between soil nutrients or soil physical properties measured in our study with the abundance of Gram negative bacterial PLFAs (data not shown).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…It has been suggested that fire only causes short term changes in soil microbial communities while larger changes may be driven by vegetation dynamics (Hart et al, 2005). Therefore, differences in soil microbial communities were presumably indirectly related to burning through changes to nutrient and substrate availability via changes in aboveground vegetation observed at the same site (Burton et al, 2010(Burton et al, , 2011. There were no correlations between soil nutrients or soil physical properties measured in our study with the abundance of Gram negative bacterial PLFAs (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…Lignin:N ratio under 5 FPD was not significantly different from 0 FPD. One explanation for this may due to the greater abundance of forbs and legumes in the more frequently burned site (Burton et al, 2011). It has been reported that burning in oak savannas can lead to an ecosystem-level N limitation due to volatilization of N. Loss of N through volatilization can result in low plant tissue quality, which in turn may lead to slower decomposition rates (Reich et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our study, fire can increase richness and diversity of species, however, such an increase is different with respect to repetition and number of fire incidents. Burton et al (2011) found that species overall diversity, coverage and richness in oak forests could significantly increase from zero to five by repetition of fire incidence during a decade.…”
Section: Discussionmentioning
confidence: 98%